The Effect Of Competence And Work Discipline On Employee Performance Of The Jakarta-Bandung High-Speed Train Project - Yulianto, Wahyu; Nusannas, Iman Sidik; Haritsah, Tania Ainun (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
ABSTRACT This study aims to determine the effect of competence on employee performance, to determine the effect of work discipline on employee performance and to determine the effect of competence and work discipline on employee performance of the Jakarta-Bandung high-speed train project. This study uses a quantitative research model. The method used in this study is the proportional stratified random sampling method, with a sample of 79 respondents from employees of PT.Sinohydro Co., Ltd. Section 2. The data collection technique uses a questionnaire that has been tested for validity and reliability using IBM SPSS 25. The results of this study indicate that the two independent variables have a positive effect on the dependent variable. The competence variable has a positive effect of 0.615 with a significance level of 0.000. The work discipline variable has a positive effect of 0.463 with a significance level of 0.000. The R square of the two variables is 0.739 or 73.9% and the remaining 26.1% is influenced by construction outside the research variables, which means that these two variables have an influence on the employee performance variable. Keywords : Competence, Employee Performance, Work Discipline